The Effect of Firm Size on Information Content of Earning Announcement - Mohsen Khoshtinat; Soghra Barari Nokashti (مطالعات تجربی حسابداری مالی, 2006)
Financial statements release and announcement earnings convey some information to the capital market and causes changes in price and exchange volume of stocks. Accountants concern with such questions as: is there a relationship between accounting and the stock price changes and the abnormal returns around the date of annual and do convey any information to the capital market? And do announcement earnings have any informational content? Since unexpected stock returns of some companies after the announcement earnings is more than the other companies, it may raise a question that why the market reaction to the good and bad news of some companies is more and greater than if s reaction to other? There are many factors affecting earnings response coefficient. The size of the company is one of these factors and has been examined more frequently in the literature and has been recognized as a powerful factor affecting informational content of financial statements and more specially announcement earnings. So our research has some questions as below: 1-        - Do stockholders respond to announcement earnings news? 2-              Is coefficient of respond to announcement earnings different among the companies of different size? To find the answer of these questions we have studied a sample consisting of l O I companies during a 3 years period stating from 1382 (1382 to l384). The results of our research show that there is a meaningful relation between the annual announcement earnings and unexpected return around the date of declares. But the quantities for R and   R2    show a   direct   weak   relation.   Then to consider   the second question we first classified the companies   in to three classes:    small sized, middle sized and large, based on their total assets book value and then we did separate tests for each class. There results show no meaningful relation between annual announcement earnings and unexpected returns around the declaration date in large companies. But there has been a meaningful relation i n the small and middle sized companies classes so we can conclude that there is a reverse relationship between the company size and informational context of two announcement earnings. Then there should be more focus on disclosure in small and middle sized companies because they are more important to users.